Electromechanical deformation of biological neurons: an intrinsic marker for label-free functional neuroimaging - You, Hengze (2025)
Membrane potential is fundamental to cell physiology and signaling. Conventional electrode-based electrophysiology has advanced the biophysical understanding of membrane potential and its implications in biological perceptions, cognitive intelligence, and embryonic development, but it necessitates placing an electrode on or near the cell of interest and is inherently invasive and low-throughput. Emerging optical electrophysiology techniques, such as genetically encoded voltage and calcium indicators, allow imaging of neural activity in a large field of view with high spatial resolution. Still, these techniques rely on preloading fluorophores or conducting genetic modifications to generate exogenous optical contrast of voltage changes or functional activities. Electromechanical deformations accompanying cells' membrane potential changes, which have been observed using modalities such as atomic force microscopy and interferometric imaging, can yield intrinsic contrast for label-free functional neuroimaging without affecting cell viability or other biological functions. This review consolidates experimental evidence of electromechanical deformations across diverse cell types, from mammalian cortical neurons to non-spiking cells, to provide an overview of this phenomenon and gain new perspectives to guide future research in label-free functional neuroimaging.